Fatigue of Materials at Very High Numbers of Loading Cycles Experimental Techniques, Mechanisms, Modeling and Fatigue Life Assessment (Springer Fachmedien Wiesbaden : Spektrum, 2018)
This book represents the final reports of the scientific projects funded within the DFG-SPP1466 and, hence, provides the reader with the possibility to familiarize with the leading edge of VHCF research. It draws a balance on the existing knowledge and its enhancement by the joint research action of the priority program. Three different material classes are dealt with: structural metallic materials, long-fiber-reinforced polymers and materials used in micro-electro-mechanical systems. The project topics address the development of suitable experimental techniques for high-frequency testing and damage monitoring, the characterization of damage mechanisms and damage evolution, the development of mechanism-based models and the transfer of the obtained knowledge and understanding into engineering regulations and applications. Contents New Experimental Techniques for VHCF Testing and Monitoring Mechanisms of Damage Evolution under VHCF Conditions Mechanism-based Assessment of VHCF Life of Materials Target Groups Ph.D. students and researchers in the subject of Materials Engineering Professionals and executives in the field of Mechanical Engineering, Solid State Physics and Solid Mechanics The Editor Hans-Jürgen Christ is Full Professor of Materials Engineering at the University of Siegen, Germany. The main objective of his research is a detailed understanding of the behavior of metals and alloys under complex conditions representing those in technical service of engineering materials. The correlation of microscopic processes with the resulting macroscopic changes in properties is used to reveal the relevant mechanisms and damage processes, in order to develop a better prediction of the application limits and the expected lifetime of materials under service conditions.